Physiological profile of very young soccer players - Bunc, V.; Psotta, R. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: There is still much uncertainty and debate surrounding the physiological requirements of competitive soccer. The coaching emphasis on skill development, deficiencies in fitness training, conservative training methods lead to difficulty in the scientific study of soccer. METHODS: The physiological profiles of 22 young soccer players (mean age = 8.0+/-0.3 years, body mass = 28.2+/-3.2 kg, body height = 132.4+/-4.3 cm and body fat = 19.4+/-1.6&percent;) were measured by the incremental exercise protocol on the treadmill with 5&percent; inclination. All boys systematically trained at least 2 years with a minimum of two training units per week. During preseason, they trained two times per week, and during the competitive season they trained at least three times and competed in one or two games per week. RESULTS: Mean VO2maxakg-1 was 56.7+/-4.9 mlakg-1amin-1. Mean value of maximal running speed on a treadmill with 5&percent; of inclination was 12.0+/-0.9 kmah-1. Mean values of Rmax = 1.11+/-0.07. The selected functional variables at the ventilatory threshold (VT) level corresponded to VO2akg-1 = 42.9+/-5.0 mlakg-1amin-1, mean values of &percent;VO2maxakg-1 at VT level were 76.5+/-1.3&percent;, mean speed of running was 10.5+/-1.2 kmah-1, mean values of &percent;Vmax at VT level were 87.5+/-1.9&percent;. The mean of energy cost of running was 4.28+/-0.19 Jakg-1am-1. According to our results, we can conclude that the physiological characteristics of young soccer players about 8 years old should be as follows: VO2maxakg-1 higher than 55 mlakg-1amin-1 in defenders, and higher than 60 mlakg-1amin-1, in midfielders and forwards. Maximal speed of running on the treadmill with 5&percent; of inclination should be higher than 12 kmah-1 in all players, the running speed at anaerobic threshold (5&percent;) higher than 10.5 kmah-1, &percent;VO2max at anaerobic threshold level higher than 77.0&percent;, and the energy cost of running lower than 4.20 Jakg-1am-1. CONCLUSIONS: As in other sports where skills play a decisive role, the physiological data cannot be the sole predictor of competitive success. On the other hand, we must note that these physiological norms and standards are necessary conditions for success in high levels of soccer competition. The norms play decisive role in talent selection.